Pratique de l’équitation au Moyen Âge d’après les textes littéraires - Pascale Bourgain (In Situ)
In the course of tales, holymen’s lives, sermons, epics, letters, medieval authors let us catch a glimpse on the ways of making use of horses in everyday life : horsemen’s social prestige, economic restraints, problems of maintenance and pasture, training, dangers. Sometimes appear solicitude gestures of a traveller for his horse, attendance, and the difficulties of climbing on horseback or getting down. There are few notes about equestrian art : using spurs, and the importance of volts and pirouettes when fighting. But some notations show the affection and trust of the rider for his fellow.